Disposition Index in Active Acromegaly - Niculescu, Dan Alexandru; Dusceac, Roxana; Caragheorgheopol, Andra; Popescu, Nicoleta; Poiana, Catalina (Frontiers in Endocrinology, 2019)
Background: The relative contribution of reduced insulin sensitivity (Si) or insulin secretion to impaired fasting glucose (IFG) or diabetes mellitus (DM) has not been clarified in active acromegaly. An intravenous glucose tolerance test (IVGTT) was never used for the calculation of Si, acute insulin response (AIRg), and disposition index (DI) in this population. Our aim was to assess Si, AIRg and DI using an IVGTT in acromegaly with normal (NGT) and abnormal glucose tolerance. Methods: We performed an IVGTT in 13 patients (8 NGT, 2 IFG, and 3 DM; 5 males, age 47.9 ± 11 years, body mass index 29.7 ± 4.1 kg/m2) with active acromegaly (insulin-like growth factor-1 4.1 ± 1.3 × upper limit of normal, basal GH 29.1 ± 25 ng/mL) and 3 healthy controls (2 males, age 39 ± 3 years, body mass index 23 ± 5 kg/m2). No patient had any growth hormone- or glucose-lowering medication. Results: NGT patients had significantly lower Si than healthy controls but higher AIRg. Hyperglycemic and normoglycemic patients had similar Si. DM patients had severely diminished AIRg (5–260 pmol × min/L) while IFG patients maintained their insulin secretion (3,862 and 912 pmol × min/L). Patients with abnormal glucose tolerance (IFG + DM) had a significantly lower DI (353 ± 350) than both NGT patients (3,685 ± 2,544) and healthy controls (5,837 ± 1,894; p < 0.01 for ANOVA). Conclusions: Disposition index suggests that although reduced insulin sensitivity is characteristic of active acromegaly it is the impaired insulin secretion that mainly drives glucose intolerance. The clinical utility of DI in predicting DM in acromegaly must be further investigated.